PENGARUH STRATEGI BISNIS DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Dewi Kusuma Wardani; Desi Khoiriyah (AKUNTANSI DEWANTARA, 2018)
This study aimed to examine the effect of business strategy and corporate characteristics on tax avoidance. The theory used in this research is agency theory. The sample that used in this research are manufacturing company during 2012-2016, based on purposive sampling method was obtained 12 companies. Variable business strategy use 2 strategies by companies is defender and prospector measured using variable dummy. Corporate characteristics used in this study is the profitability measured by the ratio of ROA, leverage, and size. The dependent variable using CETR proxy. The data in this research was processed using SPSS with multiple linear regression method. The results of this research shows that the profitability and size have a significant influence to the tax avoidance. Based on the test results, obtained a significance value of 0,010 and 0,037. Business strategies and leverage do not have influence to the tax avoidance.Â Keywords: business strategy, corporate characteristics, leverage, profitability, size, andÂ  tax avoidance.Â